2014
DOI: 10.7785/tcrtexpress.2013.600277
|View full text |Cite
|
Sign up to set email alerts
|

Multigating, a 4D Optimized Beam Tracking in Scanned Ion Beam Therapy

Abstract: The treatment of moving tumors with a scanned ion beam is challenging due to interplay effects and changing beam range. We propose multigating, as a method for 4D-treatment optimization and delivery. In 3D beam tracking, tracking vectors are added during delivery to beam spot positions based on the detected motion phase. This has the disadvantage of dose errors in case of complex motion patterns and an uncertain out-of-target dose distribution. In multigating, the motion phase for each beam spot is predefined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Only a few studies in 4D optimization have been published in particle therapy (4750). In the aforementioned literature, phase-specific plans, or the so-called 4D raster treatment plans (RST) (51), which describe which beam spots are to be delivered to which motion phase, are generated.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies in 4D optimization have been published in particle therapy (4750). In the aforementioned literature, phase-specific plans, or the so-called 4D raster treatment plans (RST) (51), which describe which beam spots are to be delivered to which motion phase, are generated.…”
Section: Introductionmentioning
confidence: 99%
“…IMPT is precise but is sensitive to uncertainties caused by patient setup and range uncertainties, respiratory motion, and anatomic changes . Several robust optimization methods have been proposed and have been shown to have great advantages by achieving robust plans while maintaining high plan quality . Unfortunately, in proton therapy besides uncertainties, there are machine hardware constraints, for example, field‐size constraint, minimum–maximum energy constraint, dose‐rate constraint for synchrotron‐based proton therapy systems, and minimum–maximum monitor unit (MU) constraint.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Several robust optimization methods have been proposed and have been shown to have great advantages by achieving robust plans while maintaining high plan quality. 2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Unfortunately, in proton therapy besides uncertainties, there are machine hardware constraints, for example, field-size constraint, minimum-maximum energy constraint, dose-rate constraint for synchrotron-based proton therapy systems, and minimum-maximum monitor unit (MU) constraint. Among them, the minimum MU constraint is the most prominent one.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of rescanning method and the magnitude of minimization of the interplay effect are strongly dependent on the specific characteristics of the irradiation system (scanning speed, beam energy change time, beam spot size, number of beam fields etc.). Therefore, it has been shown that it is especially beneficial to combine several motion mitigation techniques such as rescanning and gating or tracking (described in the next section) and gating . Zhang et al.…”
Section: Motion Mitigationmentioning
confidence: 99%